DOJŚCIE EMISJI PAPIERÓW WARTOŚCIOWYCH DO SKUTKU NA PRZYKŁADZIE EMISJI OBLIGACJI - Michalski, Marek (Zeszyty Prawnicze, 2016)
THE MOMENT OF CREATION OF SECURITIES ON THE EXAMPLE OF THE BONDS Summary Bonds are a type of securities that are used to raise funds for the financial needs of enterprises. These funds are considered as a money capital coming from external sources, as the bond issuer is obliged to repay the loan up to the date specified in the terms of the issue of the bonds. The process of the bond issue has been greatly simplified, so that bonds become an instrument easy to use on the financial market. The brevity of the provisions regulating the bond issue was intended to ensure that bond issue can be conducted briefly and to release the entire procedure from the burden of unnecessary rigorism. In contrast to shares, issuance of bonds is not subject to any formal restrictions in the form of entering the issue to a public register of any kind. On the other hand, brevity of the Bonds Act of 29 June 1995 leads to significant differences in interpretation. The Act on Bonds does not clearly identify the moment of creation of an effective claim. Whereas there are two legal terms defined in the Act i.e. the hand-over of bond documents, and the moment of the issuance taking place. The are no grounds, in light of the provisions of the Act on Bonds, to eqaute these two concepts. The creation of an effective receivable, i.e., one that may be claimed by legal actions of the creditor is determined by the moment of the issuance taking place, not the hand-over of the bond documents. The second step, namely the hand-over of the bond documents, from the perspective of the Law on Bonds has only a technical meaning and should not be treated as a requirement for the acquisition of the claim by the bondholder. Absence of the bond documents hand-over may affect the position of the bondholder, since it impedes the possibility to dispose of the claim, but does not deprive one of the right. The bondholders claim is created on the earlier stage and ist existance is independent of the bond document hand-over.